An automatic diagnosis model of otitis media with high accuracy rate using transfer learning - Qi, Fangyu; You, Zhiyu; Guo, Jiayang; Hong, Yongjun; Wu, Xiaolong; Zhang, Dongdong; Li, Qiyuan; Cai, Chengfu (Frontiers in Molecular Biosciences, 2024)
Chronic Suppurative Otitis Media (CSOM) and Middle Ear Cholesteatoma are two common chronic otitis media diseases that often cause confusion among physicians due to their similar location and shape in clinical CT images of the internal auditory canal. In this study, we utilized the transfer learning method combined with CT scans of the internal auditory canal to achieve accurate lesion segmentation and automatic diagnosis for patients with CSOM and middle ear cholesteatoma.We collected 1019 CT scan images from the Department of Otolaryngology, Head and Neck Surgery at Zhongshan Hospital affiliated with Xiamen University and used the nnUnet skeleton model along with coarse-grained focal segmentation labeling to pre-train on the above CT images for focal segmentation. We then fine-tuned the pre-training model for the downstream three-classification diagnosis task. Our proposed algorithm model achieved a classification accuracy of 92.33% for CSOM and middle ear cholesteatoma, which is approximately 5% higher than the benchmark model. Moreover, our upstream segmentation task training resulted in a mean Intersection of Union (mIoU) of 0.569. Our results demonstrate that using coarse-grained contour boundary labeling can significantly enhance the accuracy of downstream classification tasks. The combination of deep learning and automatic diagnosis of CSOM and internal auditory canal CT images of middle ear cholesteatoma exhibits high sensitivity and specificity.